ANALISIS KETERAMPILAN SISWA DALAM MELAKSANAKAN PRAKTIKUM PADA MATERI GERAK LURUS DI SMA - Medya Sartika; Zuhdi '; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to describe the student's skills in performing laboratory work for a straight motion of matter in senior high school. This research is a descriptive with supporting of quantitative approach while the method for surveying. The sample in this research is class X IPA 1 and class X IPA 2 with a total of 67 students. The selection of the samples was done by purposive sampling method. The data in this study a score of student skills in carrying out laboratory work in a straight motion of matter in high school which is analyzed descriptively, including scoring, metabulation for the average statements contained in the questionnaire, and then categorize it in accordance with the predicate implement practical skill level. Result of this is derived from the aspects of the preparation, execution, and cover. Based on data analysis of skills levels on aspects of the preparation obtained a score of 3.35 with quite good category, on the execution aspect obtained a score of 3.25 with quite well category and cover aspects of 3.49 with quite good category. Therefore, it can concluded that the class X IPA IPA 1 and X IPA 2 in SMA Negeri 14 Pekanbaru has the skills to implement a practical work in a straight motion of matter which is implemented optimally.